2021
DOI: 10.1097/jte.0000000000000206
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Practices of Exemplary Clinical Education Leaders

Abstract: Introduction: Despite frequent turnover and stress in both Director of Clinical Education (DCE) and Site Coordinator of Clinical Education (SCCE) positions, there are those who demonstrate longevity and success in these roles. Review of the Literature: A recent regional investigation found that successful DCEs and SCCEs share characteristics common to exemplary leaders. e purpose of this qualitative study was to confirm if characteristics of DCEs and SCCEs who demonstrate longevity and success are consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…6,9 Many view the DCE as a leadership position within professional programs; however, this may depend on the type of institutional employment. 4,6 Recently, LaFay et al 4 postulated longevity in the DCE position could be attributed to the leadership qualities of the individual; however, we believe it is also plausible that person-job fit and task-fit alignment may also affect successes within the position.…”
Section: Review Of the Literaturementioning
confidence: 81%
See 2 more Smart Citations
“…6,9 Many view the DCE as a leadership position within professional programs; however, this may depend on the type of institutional employment. 4,6 Recently, LaFay et al 4 postulated longevity in the DCE position could be attributed to the leadership qualities of the individual; however, we believe it is also plausible that person-job fit and task-fit alignment may also affect successes within the position.…”
Section: Review Of the Literaturementioning
confidence: 81%
“…e DCE position has emerged as a topic of scholarly interest in the past decade. [4][5][6] e DCE is a core faculty member within a professional program; however, the roles and responsibilities associated with the position are often viewed as nontraditional when compared with other faculty lines. 4,[6][7][8] e position has grown significantly because of increased class sizes, additional clinical education experiences, and challenges associated with clinical placements.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][5][6][7][8] On the CE site side, employer support is also essential. 13,32,33 One study found that successful CE faculty thrive in environments that convey trust in employee capabilities and offer autonomy to complete duties. 33 Academic program supports have also been shown to be important.…”
Section: Supports For Clinical Education Facultymentioning
confidence: 99%
“…13,32,33 One study found that successful CE faculty thrive in environments that convey trust in employee capabilities and offer autonomy to complete duties. 33 Academic program supports have also been shown to be important. 20,34,35 e Director of Clinical Education (DCE) acts as a bridge between the academic program and CE sites, serving as a resource to CE faculty.…”
Section: Supports For Clinical Education Facultymentioning
confidence: 99%